A Study On The Effect Of Partnership Quality On Business Process Outsourcing For Banks And Financial Institutions In Malaysia - Ee, Ooi (2005)
This research studied the effect of partnership quality on business process outsourcing for banks and financial institutions in Malaysia. A theoretical framework was developed to test partnership quality as critical success factors to outsourcing success. There were five partnership quality variables in the proposed model – business understanding, commitment, communication, age of relationship and top management support together with partnership trust level as mediating variable.